Opuesto de un nmero racional. Aplicacin - Ybaez Avila, Karina Lizett (2018)
The work of professional proficiency was entitled "System of rational numbers (Q)"; whose development of the learning session has been based on bibliographical references and other sources of consultation, as well as application of knowledge acquired during the academic years of my training and according to the work done during the last years. Whose conclusions indicate that; students are more committed in the mathematical area when they present problems related to everyday life. The competence developed in this class corresponds to "Act and think mathematically in situations of quantity._x000D_ Students should develop and use strategies to solve problems that represent rational numbers and their opposite on the number line and develop and use strategies to solve problems about the opposite of rational numbers. The didactic processes allow to organize better the learning of the students, organizing their knowledge in an orderly and coherent way. Teamwork allows the group to integrate all students, being recommended for better learning. Have a lot of consideration of each strategy, since knowledge is built from different criteria.